Pemetaan Pengetahuan Pustakawan Terhadap Layanan Pendukung Riset - Santosa, Faizhal Arif; Arumdini, Savira; Widuri, Noorika Retno (Jurnal IPI (Ikatan Pustakawan Indonesia), 2023)
In the environment of special libraries, the library service ecosystem is developing very rapidly as one of the research supports. The competence of the librarian also follows the development of the ecosystem needed. After the merging of National Research and Innovation Agency (BRIN), a review of the knowledge and skills possessed by librarians within the BRIN is needed to support functions and tasks. This study aims to map the librarian's knowledge ability to research support services, especially in information discovery and bibliometric services using the x-means algorithm. Using questionnaire data that was distributed to 85 BRIN librarians and library staff. The questionnaire is divided into two (2) parts, namely information discovery services and bibliometric services. The statement uses a numerical scale of 0 to 10, where 0 means incapable or not understand a concept and 10 has the meaning of being very capable of understanding a proposed concept. The x-means and k-means algorithms are used to classify librarians based on their abilities in each service using a Euclidean distance numerical measure. The results showed that the use of the x-means method for mapping the knowledge of librarians at BRIN was able to work better than k-means in the cluster range tested, both for information discovery services and bibliometric services. In total, five clusters became the most optimal cluster model in this study. In general, most BRIN librarians have the ability to provide research support services.